Структура та динаміка інвалідності внаслідок цукрового діабету в осіб молодого віку в Тернопільській області - Вернигородська, М. В.; Вернигородський, В. С.; Забур'янова, В. Ю.; Яворовенко, О. Б.; Банадига, І. Ф. (Clinical Endocrinology and Endocrine Surgery, 2014)
The results of the data analysis of primary disability due to diabetes mellitus in the population of working age in Ternopil region for the period 2007-2011 with a detailed description contingent of young people with disabilities are presented in the article. It was founded that the level of primary disability due to diabetes among people of working age in the dynamics of the 5-year decreased slightly and amounted to 1,6 per 10,000 of the population concerned. The share of young people with disabilities during the observation period was equal to an average of 45,1%. In the structure of primary disability dominated disabled group III (76,6%), disabled group II were 20,6% and I group – 2,8%.